Effect of land configuration and integrated nutrient management on growth, quality and yield of tuberose (Polianthes tuberosa) var. Prajwal - CHAWLA, S L; PATEL, M A; PATIL, SUDHA; BHATT, DIPAL; PATEL, R B (The Indian Journal of Agricultural Sciences, 2018)
Present investigation was carried out to standardize the land configuration and nutrients for better quality and yield of tuberose (Polianthes tuberose L) spikes on heavy black soil of Navsari (Gujarat) during 2011-12 to 2013-14. The experiment was laid out in split-plot design having four levels of land configuration (main plot) and three levels of nutrients (sub plot).The results indicated that planting of tuberose bulbs in 3 rows on raised bed (90 cm width) recorded significantly early sprouting (21.73 days) with maximum sprouting percentage (98.28), plant height (65.10 cm), leaves/plant (76.79), leaf area (105.24 cm2), florets/spike (43.52), rachis length (32.38 cm), spike length (102.46cm), spike duration (16.00 days), vase life (13.55 days), spikes/plant (2.45), spikes/ha (188850.31), bulbs/plant (13.09), bulbs/ha (1030790) and bulblets/plant (29.11). In nutrient management, application of fertilizer dose (300:200:100NPK kg/ha/year) along with FYM @ 15 t/ha/year recorded early sprouting (23.15 days) with maximum sprouting percentage (96.04), plant height (63.44 cm), leaves/plant (71.16), leaf area (99.56 cm2), florets/spike (39.93), rachis length (30.99 cm), spike length (97.94 cm), spike duration (14.18 days) and vase life (12.07 days), spikes/plant (2.23), spikes/ha (195577.74), bulbs/ plant (10.63), bulbs/ha (928560.00) and bulblets/plant (28.83). Raised bed planting had favourable effect on growth and yield of tuberose as compared to ridge and furrow and flat bed planting.